PP2A‐B′γ modulates foliar trans‐methylation capacity and the formation of 4‐methoxy‐indol‐3‐yl‐methyl glucosinolate in Arabidopsis leaves. (5th December 2016) - Rahikainen, Moona; Trotta, Andrea; Alegre, Sara; Pascual, Jesús; Vuorinen, Katariina; Overmyer, Kirk; Moffatt, Barbara; Ravanel, Stéphane; Glawischnig, Erich; Kangasjärvi, Saijaliisa
Significance Statement: Glucosinolates (GSL), structurally diverse secondary compounds in crucifers, act as deterrents against aphids and microbial pathogens and consequently have commercial and ecological impacts. Transcriptional control of GSL biosynthesis and modification is understood, but post‐translational modifications that determine structural variation has not been reported. It was known that protein phosphatase 2A (PP2A controls such stress‐induced metabolic adjustments. Here we show that the PP2A regulatory subunit B'γ modulates cellular trans‐methylation capacity and thus the formation of specifically methoxylated indole glucosinolates in Arabidopsis thaliana . Summary: Glucosinolates (GSL) of cruciferous plants comprise a major group of structurally diverse secondary compounds which act as deterrents against aphids and microbial pathogens and have large commercial and ecological impacts. While the transcriptional regulation governing the biosynthesis and modification of GSL is now relatively well understood, post‐translational regulatory components that specifically determine the structural variation of indole glucosinolates have not been reported. We show that the cytoplasmic protein phosphatase 2A regulatory subunit B′γ (PP2A‐B′γ) physically interacts with indole glucosinolate methyltransferases and controls the methoxylation of indole glucosinolates and the formation of 4‐methoxy‐indol‐3‐yl‐methyl glucosinolate in Arabidopsis leaves. By taking advantage of proteomic approaches and metabolic analysis we further demonstrate that PP2A‐B′γ is required to control the abundance of oligomeric protein complexes functionally linked with the activated methyl cycle and the trans ‐methylation capacity of leaf cells. These findings highlight the key regulatory role of PP2A‐B′γ in methionine metabolism and provide a previously unrecognized perspective for metabolic engineering of glucosinolate metabolism in cruciferous plants.